Urinalisis Menggunakan Dua Jenis Dipstick (Batang Celup) pada Sapi Bali - Harjono Utama, Iwan; Marieti Hutagalung, Evi; Puspa Ari Laxmi, I Wayan; Krisna Erawan2,, I Gusti Made; Kayati Widyastuti, Sri; Eka Setiasih, Luh; Berata, Ketut (Jurnal Veteriner, 2012)
This study aimed to compare two kind of urinalysis dipsticks normaly used for human, for used in balicattle. A total of 100 urine samples were collected from 78 bulls and 22 cows ages between 4-7 years old.Each sample was kept in a plastic bottle and labelled until urinalysis was performed. Both dipstickshowed different urin chemical analysis results, except for nitrite. However, in general both dipsticksshowed consistency urinalysis results. Therefore, the two dipsticks can be used for urinalysis in balicattle.
Keywords: bali cattle, urinalysis